Silver Nano/Microparticles Modification and Applications 2.0 - Jun, Bong-Hyun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Currently, nano/microparticles are widely used in various fields. Silver particles are one of the most vital of the various particles, due to their unique optical-physical-chemical properties. The developed materials have been proposed for use in various fields such as in biosensors, diagnostics, imaging, catalysts, solar cells, and as antibacterials. Their unique, size-dependent plasmonic properties render the particles superior in biomedical applications. This importance of silver materials led to the first edition of Silver Nano/Microparticles: Modification and Applications, which was successfully published last year with ten outstanding papers. This second edition of the Special Issue also provides original contributions detailing the synthesis, modification, and applications of silver materials. Eleven outstanding papers which describe examples of the most recent advances in silver nano/microparticles are included.